Newly isolated halotolerant Gordonia terrae S-LD serves as a microbial cell factory for the bioconversion of used soybean oil into polyhydroxybutyrate - Song Xu; Ruiqin Han; Lidan Tao; Zhipeng Zhang; Junfei Gao; Xinyuan Wang; Wei Zhao; Xiaoxia Zhang; Zhiyong Huang (Biotechnology for Biofuels and Bioproducts)
Abstract Polyhydroxybutyrate (PHB) is a class of biodegradable polymers generally used by prokaryotes as carbon sources and for energy storage. This study explored the feasibility of repurposing used soybean oil (USO) as a cost-effective carbon substrate for the production of PHB by the strain Gordonia terrae S-LD, marking the first report on PHB biosynthesis by this rare actinomycete species. This strain can grow under a broad range of temperatures (25–40 ℃), initial pH values (4–10), and salt concentrations (0–7%). The findings indicate that this strain can synthesize PHB at a level of 2.63 ± 0.6 g/L in a waste-containing medium containing 3% NaCl within a 3 L triangular flask, accounting for 66.97% of the cell dry weight. Furthermore, 1H NMR, 13C NMR, and GC–MS results confirmed that the polymer was PHB. The thermal properties of PHB, including its melting (Tm) and crystallization (Tc) temperatures of 176.34 °C and 56.12 °C respectively, were determined via differential scanning calorimetry analysis. The produced PHB was characterized by a weight-average molecular weight (Mw) of 5.43 × 105 g/mol, a number-average molecular weight (Mn) of 4.00 × 105 g/mol, and a polydispersity index (PDI) of 1.36. In addition, the whole genome was sequenced, and the PHB biosynthetic pathway and quantitative expression of key genes were delineated in the novel isolated strain. In conclusion, this research introduces the first instance of polyhydroxyalkanoate (PHA) production by Gordonia terrae using used soybean oil as the exclusive carbon source, which will enrich strain resources for future PHB biosynthesis.